Alternative splicing of hTERT: a further mechanism for the control of active hTERT in acute myeloid leukemia. Issue 3 (4th March 2018) - Calvello, Celeste; Rocca, Barbara; Klersy, Catherine; Zappatore, Rita; Giardini, Ilaria; Dambruoso, Irene; Pasi, Francesca; Caresana, Marilena; Zappasodi, Patrizia; Nano, Rosanna; Boni, Marina; Bernasconi, Paolo
Abstract: hTERT component is the key regulator of telomerase. Alternatively spliced variants of hTERT generate different telomerase activity. The goal of the study was to determine the role of different hTERT isoforms in the regulation of telomerase expression in AML patients. Among the 97 studied patients, 45 had a complex karyotype and 52 a normal karyotype. hTERT isoforms expression was determined in bone marrow samples by q-RT-PCR, using SYBR Green I. hTERT expression was lower in AML patients than controls (median 2.5 vs. 10.1, p = .003), though no difference was observed between the complex and normal karyotype (median 3.2 vs. 2.3, p = .37). High trans-dominant negative isoform expression increased the response rate by two. High expression of inactive product (–α – β) was shown to increase the risk of relapse by about three times. In conclusion, our data suggest an intriguing link between the control of hTERT isoforms expression and AML outcome.